PENENTUAN UKURAN BULIR DAN JENIS DOMAIN MAGNETIK GUANO DARI GUA RANTAI DAN GUA SOLEK DI KECAMATAN LAREH SAGO HALABAN KABUPATEN 50 KOTA DENGAN METODE ANHYSTERETIC REMANENT MAGNETIZATION (ARM) - Nilam Sari (PILLAR OF PHYSICS, 2013)
Magnetic properties of Guano can be seen from the concentration of magnetic minerals, grain size, domain type and type of magnetic minerals. From the magnetic susceptibility measurements was found that there is concentration of magnetic minerals in the guano. This research will be studied about grain size and type of magnetic domains from Rantai and Solek Cave, Lareh Sago Halaban Subdistrict, 50 Kota District. Grain size and type of magnetic domains can be identified by matching the decay curve of Anhysteretic remanent Magnetization (ARM) of sample with Lowrie-Fuller Test standard curve and King's Plot. The instrument used in this research are Molspin AF Demagnetizer and Minispin Magnetometer. The determination results of grain size and type of magnetic domain Rantai Cave have variation with the range between <0.1 μm - >135 μm with type of  domain magnetic is single domain (SD), pseudo single domain (PSD) and multi domain (MD). Guano samples of Solek Cave having grain sizes of magnetic between 2 μm-135 μm where magnetic domains are pseudo single domain (PSD) and multi domain (MD). Keywords: Guano, grain size, magnetic domain, Anhysteretic Remanent Magnetization (ARM).